ANALISIS STATISTIK PARAMETRIK PERBEDAAN SIGNIFIKAN DALAM KENAIKAN HARGA AYAM DI PASAR SEJAHTERA KABUPATEN BEKASI - Rifky Tri Nugroho; Qeis Al Gifari Abdullah, Dwi Ali Ega Fauzi, Teuku Alfiansyah, Abizard Haykal, Aji Dewa Abdullah, Fah (CV. Adiba Aisha Amira, 2024)
This study aims to help provide answers whether the increase in chicken prices at Pak Selamet's umkm in the prosperous market in the last three years, the difference in price increases is still considered significant or not. This research applies the one-way ANOVA test to ensure statistical quality and applies a quantitative approach through descriptive data collection using observation and interview techniques. Based on the findings of the ANOVA test which obtained the results of the P-Value <0.05 which concluded that there was a significant difference, it can be stated that the price increase of domestic chicken and native chicken in the Sejahtera market in Bekasi Regency in the last three years, especially Pak Selamet's umkm, experienced a significant difference in price increases per year. But in the follow-up test, namely the Tukey test (POST HOC TEST) on the price of native chicken in 2022 - 2023 there was no significant price increase in that year.